Al-Ghororu Wa Atsaruhu Fi Tijaroh Al-Ma'kulah Al-Mu'asharoh - Suratno Suratno (Sanaamul Quran: Jurnal Wawasan Keislaman, 2021)
This research is motivated by the curiosity of the ghoror influence on several forms ofmodern culinary business because since the end of 2019 several restaurants have gone viral for selling their food menus with the "All You Can Eat" system and some are using the sales system "Pay as much as you like to eat as much as you like" or so-called "Pay What You Want". The formulation of the problems of this research are: 1) What are the good criteria that can influence the law of buying and selling? 2) What is the effect of ghoror on the sales system with "All You Can Eat" and the sales system "Pay as much as you can eat as you like"? This paper includes qualitative research by conducting literature reviews of several sources from ulama›s books and various papers, as well as several sources from trusted websites on the internet. From this research, the authors conclude that: 1) The criteria of ghoror that can affect the law of sale are: ghoror is heavy, there is no need (hajah) syari in the contract, ghoror occurs at the main object of the contract, ghoror occurs in the mu›awadhah contract (business transactions). 2) Strong opinion on sales with the "All You Can Eat" system that this kind of ghoror is legal (light) and does not affect the contract. As for the sale with the system "Pay as Sincerely as you eat as you like" there is uncertainty about the price and the product being sold, the ghoror, in this case, is heavy, and affects the contract,therefore buying and selling using this system is prohibited by law.Keywords: ghoror, business, culinary, All YouCan Eat, All you can eat, pay as much as youwant ABSTRAKPenelitian ini dilatarbelakangi oleh keingintahuanbpengaruh ghoror terhadap beberapa bentuk bisnis kuliner modern, karena semenjak akhir tahun 2019 beberapa restorant viral karena menjual menu makananya dengan sistem “All You Can Eat “ dan ada pula yang memakai sistem penjualan “ Bayar Seikhlasnya Makan Sepuasnya “ atau biasa disebut “ Pay What You Want “ .Rumusan masalah dari penelitian ini adalah: 1) Apa saja kriteria ghoror yang bisa mempengaruhi hukum jual beli ? 2) Apa pengaruh ghoror pada sistem penjualan dengan “All You Can Eat “dan sistem penjualan “ Bayar Seikhlasnya Makan Sepuasnya “? Makalah initermasuk penelitian kualitatif dengan melakukan kajian pustaka terhadap beberapa sumber dari kitab-kitab ulama dan berbagai makalah, serta beberapa sumber dari website terpercaya di internet. Dari penelitian ini, penulis menyimpulkan bahwa: 1) Kriteria ghoror yang bisa mempengaruhi hukum penjualan adalah: ghoror tersebut berat, tidak ada kebutuhan (hajah) syar’i dalam akad, ghoror terjadi pada pokok objek akad, ghoror terjadi pada akad mu’awadhah (transaksi bisnis). 2) Pendapat yang rojih pada penjualan dengan sistem “All You Can Eat “ bahwa ghoror seperti ini yasir (ringan) dan tidak mempengaruhi akad. Adapun penjualan dengan sistem “Bayar Seikhlasnya Makan Sepuasnya “terdapat ketidakjelasan harga dan produk yang dijual, ghoror dalam hal ini berat, dan mempengaruhi akad, maka dari itu jual beli dengan sistem seperti ini dilarang secara syariat. Kata kunci : ghoror , bisnis, kuliner, All You Can Eat, Makan sepuasnya bayar seikhlasnya